2021
DOI: 10.3892/mmr.2021.12236
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lncRNA SNHG8 plays a protective role in hypoxia-ischemia-reoxygenation-induced myocardial injury by regulating miR-335 and RASA1 expression

Abstract: long non-coding (lnc)rnas serve a role in a number of diseases, including different types of cancer and acute myocardial infarction. The aim of the present study was to investigate the protective role of lncrna small nucleolar rna host gene 8 (SNHG8) in hypoxia-ischemia-reoxygenation (Hi/r)-induced myocardial injury and its potential mechanism of action. cell viability, proliferation, creatine kinase myocardial band, cell apoptosis and protein expression levels were determined by cell counting Kit-8 assay, edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The lncRNA HLA complex group 11 has been shown to diminish the malignancy of non-small-cell lung cancer by reducing the expression levels of carcinogenic microRNA875 [ 13 ]. However, transfection with lncRNA short nucleolar RNA host gene eight reduced RASA1 expressions, shielding H9C2 cells against HI/R damage [ 14 ]. Nonetheless, the association of lncRNAs with immune cell infiltration in ironophilic cell disease is yet unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA HLA complex group 11 has been shown to diminish the malignancy of non-small-cell lung cancer by reducing the expression levels of carcinogenic microRNA875 [ 13 ]. However, transfection with lncRNA short nucleolar RNA host gene eight reduced RASA1 expressions, shielding H9C2 cells against HI/R damage [ 14 ]. Nonetheless, the association of lncRNAs with immune cell infiltration in ironophilic cell disease is yet unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, experiments concerning the functional role of lncRNAs were performed under experimental animal models or by in vitro assays. Some studies revealed the active role of lncRNAs in cell autophagy (Liang et al, 2020;Zhang and He, 2020;Li J. et al, 2021), apoptosis (Zhu et al, 2018;Gong et al, 2019;Zhang D. et al, 2019, Zhang M. et al, 2019Zhou et al, 2019;Huang L. et al, 2020;Liao et al, 2020;Lv et al, 2020;Yan et al, 2020;Zhang Y. et al, 2020;Zhou et al, 2020;Liu et al, 2021;Zhu et al, 2021a, 1), cardiac fibrosis (Wang X. et al, 2018, 30;Huang et al, 2019;Sun F. et al, 2019;Zhang JC. et al, 2019, 21;Lang et al, 2021;Zhang H. et al, 2021, 155-5), cardiac remodelling Zhang B.f. et al, 2020), inflammation, and angiogenesis (Chen ZL.…”
Section: Lncrna/circrna-mirna-mediated Interactionmentioning
confidence: 99%
“…In non-small cell lung cancer, the LNCRNA HLA complex group 11 was demonstrated in reducing malignancy by eliminating the expression levels of carcinogenic microRNA875 [ 14 ]. However, transfection with LNCRNA short nucleolar RNA host gene eight reduced RASA1 expressions, shielding H9C2 cells against HI/R damage [ 15 ]. In recent years, ferroptosis of tumor cells has attracted a lot of attention as a new type of cell death that enables tumor cells in overcoming treatment resistance [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%